2018
DOI: 10.1111/jocn.14015
|View full text |Cite
|
Sign up to set email alerts
|

“My mentor didn't speak to me for the first four weeks”: Perceived Unfairness experienced by nursing students in clinical practice settings

Abstract: Exploring student nurse perceptions of their learning is important when attempting to enhance educational practice in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 38 publications
(63 reference statements)
5
59
0
6
Order By: Relevance
“…Finally, to improve mentoring in clinical learning environments, regular mentor education needs to be planned together with the goals for nurses' individual career growth. Education is valuable for enhancing mentoring competence according to O'Brien et al (), and both mentors and students have expressed wishes for further basic and advanced level education (Hvalič‐Touzery et al, ; Jack et al, ; Pitkänen et al, ). Education helps mentors not only to develop pedagogical competences, but also to improve their knowledge of nursing curricula and bridge the theory‐practice gap, which often hinders clinical learning and contributes to the shock of transition from undergraduate education to a professional nursing career (Duchscher, ; Lavoie‐Tremblay et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, to improve mentoring in clinical learning environments, regular mentor education needs to be planned together with the goals for nurses' individual career growth. Education is valuable for enhancing mentoring competence according to O'Brien et al (), and both mentors and students have expressed wishes for further basic and advanced level education (Hvalič‐Touzery et al, ; Jack et al, ; Pitkänen et al, ). Education helps mentors not only to develop pedagogical competences, but also to improve their knowledge of nursing curricula and bridge the theory‐practice gap, which often hinders clinical learning and contributes to the shock of transition from undergraduate education to a professional nursing career (Duchscher, ; Lavoie‐Tremblay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Good experiences in mentoring increase nurses' retention (Ward & McComb, 2018), and positive attitudes, engagement and dedication of healthcare workers enhance learning environments (Tomietto et al, 2016). In addition, planning clinical practices improves mentors' attitudes (O'Brien et al, 2014), and mentors play important roles as role models (ideally displaying high levels of professional patient-centredness and leading by example) in developing students' professional identity (Felstead & Springett, 2016 Jack et al, 2018;Pitkänen et al, 2018). Education helps mentors not only to develop pedagogical competences, but also to improve their knowledge of nursing curricula and bridge the theory-practice gap, which often hinders clinical learning and contributes to the shock of transition from undergraduate education to a professional nursing career (Duchscher, 2009;Lavoie-Tremblay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study highlighted one important source of such willingness (rapport). Jack et al (2018) indicated that unfair treatment in mentorship during clinical practice can lead to nursing students' intention to leave the nursing profession. Like Jack et al (2018), this study examines the impact of mentorship on nurses' professional turnover intentions.…”
Section: Discussion On the Nonsupported Hypothesesmentioning
confidence: 99%
“…Mentorship (or peer-mentoring) refers to the structural support that a mentor provides to ensure role transition and talent development among mentees (Tiew, Koh, Creedy, & Tam, 2017). Mentorship has been shown as crucial to nursing students during clinical placement (Jack et al, 2018). Effective mentorship could reduce anxiety among nursing students (Sprengel & Job, 2004) and helps them persist in their educational programmes (ten Hoeve, Castelein, Jansen, & Roodbol, 2017).…”
Section: Social Capital Theory and Mentorship In Nursingmentioning
confidence: 99%